Agronomic management for biotic stresses in crop production - Dixit, Anil; Pradhan, Adikant (Indian Farming, 2021)
In the era of climate change, good agronomic practices are need of the hour to curb the potential damage to be executed by vulnerable pathogens. The estimated potential threat due to disease incidences owing to imminent climate change is only a rough estimate based on some simulation models and studies conducted under fully controlled conditions, which seems to be realistic, if happened, the good agronomic practices will play a key role to manage the event, which is often forgotten in modern literature on plant diseases, even through many traditional farmers have adequately managed plant diseases for millennia, primarily with cultural practices, though many of them are sustainable, although some are highly labour intensive. It is important to integrate traditional cultural controls into modern pest management systems especially those for management of plant diseases, to a greater degree than has been done wonder in the past.